International Reserves in Low Income Countries : Have they Served As Buffers?. (IMF Working Papers; Working Paper ;, 2012)
This paper provides a historical perspective on the role of international reserves in low-income countries as a cushion against large external shocks over the last three decades - including the current global crisis. The results suggest that international reserves have played a role in buffering external shocks, with the resulting macroeconomic costs varying with the nature of the shock, the economy's structural characteristics, and the level of reserves.